Morpho-histology, endogenous hormone dynamics, and transcriptome profiling in Dacrydium pectinatum during female cone development - Wang, Enbo; Lu, Wenju; Liang, Haiying; Zhang, Xumeng; Huo, Shaojie; Song, Xiqiang; Wang, Jian; Zhao, Ying (Frontiers in Plant Science, 2022)
Dacrydium pectinatum de Laubenfels is a perennial dioecious gymnosperm species dominant in tropical montane rain forests. Due to deforestation, natural disasters, long infancy and poor natural regeneration ability, the population of this species has been significantly reduced and has been listed as an endangered protected plant. To better understand the female cone development in D. pectinatum, we examined the morphological and anatomical changes, analyzed the endogenous hormone dynamics, and profiled gene expression. Female reproductive structures were first observed in January. The morpho-histological observations suggest that the development of D. pectinatum megaspore can be largely divided into six stages: Early flower bud differentiation, bract primordium differentiation, ovule primordium differentiation, dormancy, ovule maturity, seed maturity. The levels of gibberellins (GA), auxin (IAA), abscisic Acid (ABA), and cytokinin (CTK) fluctuated during the process of female cone development. And female cones of D. pectinatum need to maintain a low level of GA3-IAA-ABA steady state to promote seed germination. The first transcriptome database for female D. pectinatum was generated, revealing 310,621 unigenes. Differential expression analyses revealed several floral (MADS2, AGL62, LFY) and hormone biosynthesis and signal transduction (CKX、KO、KAO、ABA4、ACO, etc) genes that could be critical for female cone development. Our study provides new insights on the cone development in D. pectinatum and the foundation for female cone induction with hormones.